The Hajj the Muslim pilgrimage to Mecca and the Holy Places - Peters, F. E. (Princeton University Press, 1994)
Among the duties God imposes upon every Muslim capable of doing so is a pilgrimage to the holy places in and around Mecca in Arabia. Not only is it a religious ritual filled with blessings for the millions who make the journey annually, but it is also a social, political, and commercial experience that for centuries has set in motion a flood of travelers across the world's continents. Whatever its outcome - spiritual enrichment, cultural exchange, financial gain or ruin - the road to Mecca has long been an exhilarating human adventure. By collecting the first-hand accounts of these travelers and shaping their experiences into a richly detailed narrative, F.E. Peters here provides an unparalleled literary history of the central ritual of Islam from its remote pre-Islamic origins to the end of the Hashimite Kingdom of the Hijaz in 1926. Air travel has now converted what was once a lengthy land or sea voyage into a matter of hours, but the accounts of that earlier, more arduous experience on foot or camelback, under sail or steam, are many and extraordinary. Although overwhelming numbers of travelers have been driven chiefly by piety and God's command, some of them have been European frauds, adventurers, or explorers drawn by the lure, and the danger, of a forbidden experience. Peters has enhanced his presentation of their accounts with an abundance of rare, and in many instances previously unpublished, nineteenth-century photographs of pilgrims and the Islamic Holy Places from the unique collection of the Harvard Semitic Museum, annotated by the curator, Dr. C.E.S. Gavin.